Acquired (autoimmune) hemophilia: demographics, outcomes, and readmissions - Aditi Sharma; Nikhil Vojjala; Vijendra Singh (Blood Vessels, Thrombosis & Hemostasis)
Abstract: Acquired hemophilia (AHA) is a rare bleeding disorder characterized by autoantibodies against coagulation factors. It predominantly affects older adults and is associated with autoimmune disorders or malignancies. Achieving hemostasis and inhibiting autoantibody production through immunosuppression are the mainstays of treatment.We conducted a retrospective cohort study using the Nationwide Readmissions Database from 2016 to 2019 to perform a descriptive analysis of AHA, including the estimation of the 30-day readmission rate and primary diagnoses at readmission.Of 1450 admissions for AHA, 803 (55.4%) were male, and the median age at admission was 73 years. Approximately 21% had an underlying solid malignancy, 3.9% had hematologic malignancy, and 13.5% had autoimmune disease. Acute myocardial infarction occurred in 9.5%, disseminated intravascular coagulation in 1.2%, intracranial hemorrhage in 1.5%, ischemic stroke in 2.5%, and venous thromboembolism in 4.4%. Bleeding occurred in 30.2% of admissions, with 27% requiring blood transfusion. The median length of hospital stay was 7 days, and there were 101 deaths during the index admission, resulting in a 7% inpatient mortality rate. Mortality was higher in the older age group at 8% compared with 3% in those aged <65 years (P = .03). The 30-day readmission rate was 27%, with a 10.8% mortality rate during readmission. Infections followed by bleeding were the most common causes for readmission. High rates of bleeding and thrombotic complications are seen in AHA, with bleeding and infection being the primary reasons for the elevated 30-day readmission rate, indicating significant treatment-related toxicity and disease relapse.